Penyuluhan Mengenai Inovasi Mengajar Dan Membangun Kelas Yang Menyenangkan Untuk Guru - Ken Heryani Sulis; Dita Juwita Zuraida; Misbah Fikrianto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Educators or teachers in carrying out innovation and creativity in quality learning are one of the important components in improving the quality of education in the current era of rapidly developing technology. Community Service activities carried out in the form of online counseling aim to increase teachers' insight in understanding students' character identification and encouraging their enthusiasm for learning, understanding learning strategies based on the character and learning styles of elementary level students, and understanding teaching innovations and building enjoyable classes. The target audience for this Community Service activity is teachers, lecturers and prospective teachers throughout Indonesia, totaling 288 participants. This extension activity is carried out in the form of a lecture method with presentation media. The stages carried out in this extension activity include: preparation, socialization and implementation. As a result of this outreach activity, 81.3% of participants felt they had an idea of ​​teaching innovation and building enjoyable classes based on a poll conducted after the presentation of the material.